Epicatechin Reduces Striatal MPP+-Induced Damage in Rats through Slight Increases in SOD-Cu,Zn Activity - M. Rubio-Osornio (Oxidative Medicine and Cellular Longevity, 2015)
Parkinson’s disease is a neurodegenerative disorder characterized by movement alterations caused by reduced dopaminergic neurotransmission in the nigrostriatal pathway, presumably by oxidative stress (OS). MPP+ intrastriatal injection leads to the overproduction of free radicals (FR). The increasing formation of FR produces OS, a decline in dopamine (DA) content, and behavioral disorders. Epicatechin (EC) has shown the ability to be FR scavenger, an antioxidant enzyme inductor, a redox state modulator, and transition metal chelator. Acute administration of 100 mg/kg of EC significantly prevented (P<0.05) the circling MPP+-induced behavior (10 μg/8 μL). Likewise, EC significantly (P<0.05) reduced the formation of fluorescent lipid products caused by MPP+. MPP+ injection produced (P<0.05) increased enzymatic activity of the constitutive nitric oxide synthase (cNOS). This effect was blocked with acute EC pretreatment. Cu/Zn-dependent superoxide dismutase (Cu/Zn-SOD) activity was significantly (P<0.05) reduced as a consequence of MPP+ damage. EC produced a slight increase (≈20%) in Cu/Zn-SOD activity in the control group. Such effects persisted in animals injured with MPP+. The results show that EC is effective against MPP+-induced biochemical and behavioral damage, which is possible by an increase in Cu/Zn-SOD activity.